Hubungan asupan energi dan zat gizi serta pengetahuan dengan status gizi pada remaja di Kota Kupang - Pantaleon, Maria Goreti; Petrika, Yanuarti; Zogara, Asweros Umbu; Desi, Desi; Niron, Maria (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Nutritional status in adolescents is a crucial factor affecting the quality of future generations. Various nutritional issues among adolescents, such as inadequate nutrient intake, anemia, and obesity, remain significant challenges in Kupang City.Objective: This study aims to analyze the relationship between energy intake, nutrient intake, and nutritional knowledge with the nutritional status of adolescents in Kupang City.Methods: This study was conducted at SMA Negeri 2, SMA Negeri 6, and SMA Negeri 7 in Kupang City using a cross-sectional approach involving 345 students. The sampling technique used was consecutive sampling. Nutritional intake data were collected through interviews using a food recall questionnaire, while nutritional status was assessed through weight and height measurements, which were then analyzed using the WHO Anthro application. Adolescent nutritional knowledge was assessed through a self-administered questionnaire. All data were processed using SPSS software and analyzed using the chi-square test.Results: The majority of respondents had good nutritional status (70,1%). Bivariate analysis showed a significant association between intake of carbohydrate (p=0,000), protein (p=0,016), energy (p=0,000), and fat (p=0,000), with nutritional status. However, the relationship between nutrition knowledge and nutritional status did not show statistical significance (p=0,917).Conclusion: There is a significant relationship between carbohydrate, protein, energy, and fat intake with adolescents' nutritional status, whereas nutritional knowledge does not have a direct impact.